(3GdaUhd aj GdJUha Yf CHj Ydi GdMSf Hf Ydi GdObGbs - (3CHh GdbGSe GdbTjQjs
(3ChdgG (B:s
(3gPg aUhd LeYgG GdGSJGP GdGeGe Rjf GdGSdGe GHh GdbGSe GdbTjQi GOGe Gdgd JCjjOg ef cdGe GdGSJGP CHj Ydi GdMSjf Hf Ydi GdObGb QMeg Gddg bGd SeYJ GdGSJGP GHG Ydi QMeg Gddg jbhd ai bhdg JYGdi (B( (3Hd jDKQhf GdMjGI GdOfjG (B) s
(3BNQgG (B:s
(3hGdeMH dGjQLi dg GaGbg hdG jMed Cf jchf HJMed GYHGFg WGbg adGjJhH Yf MGdJg dGLeY Gddg jhe MTQi EdG Ydi LfI VdhYi fLR GdcJGH hGdMeO ddg QH GdGQHGH s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GdBUajI HMjOQ CHGO (B((3ehGYX (B50) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs